The importance of electroencephalography in the diagnosis of hepatic encephalopathy due to cirrhosis – a case report - Fuksa, Katarzyna (European Journal of Clinical and Experimental Medicine, 2022)
<p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Introduction and aim. Hepatic encephalopathy (HE) associated with cirrhosis of the liver is a neuropsychiatric syndrome, with symptoms ranging from barely detectable changes to deep coma. It frequently occurs in the form of episodes and relapses and can be triggered by external factors. HE severity is graded according to the West Haven criteria. The aim of the study is to draw attention to the ever-important and often key role of electroencephalography in the diagnosis of hepatic encephalopathy, even in today’s era of increasingly advanced diagnostic methods. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Description of the case. A 57-year-old patient, professionally active at the time, was admitted to the hospital’s Neurology Department on an emergency basis due to difficulties with standing and moving, orientation disorders and limb tremor. <p class="rtejustify" style="box-sizing: border-box; margin: 0px 0px 1em; line-height: 20px; color: #010101; font-size: 14px; text-align: justify; font-family: Lato, sans-serif; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: 0.1px; orphans: 2; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial;">Conclusion. While HE pathogenesis is multifactorial, the most important factors include increased brain exposure to ammonia, intestinal dysbiosis, and endotoxemia inducing a systemic inflammatory response. Patient observation, blood laboratory tests, neuropsychological tests and neurophysiological tests (EEG and evoked potentials) play an important role in establishing the diagnosis. Treatment and secondary prevention of hepatic encephalopathy include elimination of triggers and reduction of ammonia production and improvement of its metabolism.